Analysis on socio-economics and the economic challenges of Covid-19 at household level - Zainudin, Norzalina; Md Jusoh, Zuroni; Paim, Laily; Harun, Zubaidah; Nordin, Nurnaddia; Nordin, Nurhaiza (Human Resource Management Academic Research Society, 2022)
This study examines how the COVID-19 shock affects households by drawing the economic challenges and provide an opportunities to reduce the impact of crisis. The online survey was used in the data collection which focuses on economic indicators such as income, job, salary, spending, debt, saving, and price level. The survey reveals significant association (p<0.0001) between job category, job status and age with job risk. Low income level found to have higher risk on income reduction (ChiSq=23.94, C=0.271) at this point. Part-time and contract workers are also more vulnerable when come to the risk of income cutting because of the MCO measures. Data shows, 53.8 percent of the households agree with the high price of goods and services after the pandemic. This support with 73.3 percent of households said the pandemic slightly contributes to higher spending for basic or necessary goods. Despite a number of challenges, the pandemic offers a window of opportunity for the development of household production which there is evidence of coping strategies, such as supplementing income through gig work and home gardening. Findings can be used to target interventions designed to reduce pandemic risk and the economic challenges of the COVID-19 required monitoring in real-time.